Prevention and control of multidrug-resistance tuberculosis in Ethiopia: Patients’ perspectives from the Oromia region - Reta Angessa Beyene; Elsie Janse van Rensburg (PLoS ONE, 2025)
Background Multi-drug-resistant tuberculosis (MDR-TB) is one of the biggest challenges worldwide to end tuberculosis. It is vital to understand the challenges and opportunities of patients during MDR-TB treatment to enhance prevention and control efforts. The gap in research on the challenges and opportunities of patients during the screening, diagnosis, referral, and follow-up of MDR-TB prompted this study. Purpose The purpose of the study was to assess the challenges and opportunities for patients with MDR-TB during the diagnosis and treatment of MDR-TB in the Oromia region of Ethiopia. Methods A qualitative approach was applied. The data were collected from 30 MDR-TB patients from 1 to 30 April 2022 using semi-structured interviews after written informed consent was signed by each participant to understand the challenges and opportunities of MDR-TB treatment. Data was analysed by thematic analysis using ATLAS.ti software. Result This article identifies challenges that include delays in diagnosis and treatment initiation due to inadequate diagnostic services, physical inaccessibility, and financial problems faced by patients to pay for transport, food, diagnosis, and accommodation. Other challenges included lack of psychosocial support, shortage of healthcare providers, poor communication, drug side effects, and interruption of food and housing support. In addition, participants mentioned opportunities, which include the availability of free diagnosis, treatment, and admission; availability of transport; food and housing allowance; and use of an ambulance for referral. Conclusion This study filled a research gap in Ethiopia by identifying challenges and opportunities during the MDR-TB treatment program. The MDR-TB treatment program should focus on improving inadequate screening and resources, shortage of healthcare providers, delays in the referral process, and non-compliance of patients.